THE EFFECT OF PICTURE SERIES IN TEACHING WRITING EXPLANATION TEXT AT SMA DARUSSALAMAH - Nunik Irmayanti; Dian Rahma Santoso (Journal of Higher Education and Academic Advancement, 2024)
The focus on find out whether there is an impact on students' ability to write explanatory texts using serial picture media. The respondent of picture series in writing explanation text at SMA Darussalamah for eleventh grade is twenty six respondents. The method is quantitative. The researcher used pre-experimental design. Instruments that used the researcher was pre-test and post-test. In the scoring rubric, the researcher knew that the ideal average value was 44.9 while the ideal standart deviation was 11.91. In addition, their scores in writing were getting better over time. The pre – test’s average value was 38.69; and the post-test was 52.08. Additionally, in pre-test, the standart deviation was 10.85. It means that the final results they got was homogenous because the standart deviation is lower than the ideal. Meanwhile, in the post-test, the opposite happened. Their achievement was various because their average score was higher than the ideal average score. Finally, it can be proved that using picture series had an impact on improving students’s writing skills.